Perfil Tecnológico del Cultivo de Nuez Pecán, para el Departamento de Esquina, Corrientes - Taiariol, Dario; Giancola, Silvana Ines; Rodriguez, Diego Edgardo Manuel; Estigarribia, Carlos Adolfo; Maurig, María Valentina; Vega, Osvaldo; Etchepare, Esteban; Leiva, Nelson Jose (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster